Lubelscy korespondenci Edwarda Stachury – Maria Bechczyc-Rudnicka - Pachocki, Dariusz (Tematy i Konteksty, 2018)
Edward Stachura spent three years of his life in Lublin. He enrolled at the Catholic University of Lublin in 1957, majoring in French Philology. In 1960 he moved to Warsaw and started coressodnance to Maria Bechczyc-Rudnicka who was a chief editor in local literary newspaper “Kamena”. Stachura published there some of his works. The letters which are stored in Hieronim Łopaciński Public Library in Lublin give us some information about writer’s life which he used to spend “in road” nad his works sent as attachments. We have letters of Stachura but not of Bechczyc-Rudnicka because at the end of his life he decided to burn all letters and photos directed to him. Thats why editors could not collect any dialog of correspondance. The letters have been read from the handwritten manuscripts, typescripts and edited (the language of the letters has not been changed). The letters appear in print for the very first time.